Enhancing Seismic Hazard Preparation in Lampung, Sumatra: Improved Magnitude Conversion, Seismicity Smoothing, and Area Source Modeling - Rizki Wulandari; Yudha Styawan; Chung-Han Chan (Indonesian Journal on Geoscience, 2026)
This work improves seismic hazard evaluation for the Lampung region in Sumatra by tackling the precision in magnitude conversion, attenuation of seismicity, and area-source modelling. Considering the variety magnitude. The magnitude conversion equations were initially validated using scales from historical earthquake data. And, if required, enhanced to guarantee their dependability for the area. Utilizing maximum likelihood estimation Maximum Likelihood Estimation (MLE) and ordinary. Ordinary least squares (OLS) regression was employed to compute parameters for frequency-magnitude distributions. Facilitating a comprehensive comparison that acknowledges OLS's sporadically superior alignment with observed data. Gaussian distribution smoothing was utilized diverse bandwidths (25, 50, 75, and 100 km) to illustrate spatial seismicity patterns, disclosing a distance of 50 kilometers. Bandwidth provides the most consistent model performance, especially in terms of accuracy in the Molchan illustration. The area skill score (ASS) validates the superior forecasting capacity of the smoothed seismicity models. Using bandwidths of 25, 50, and 75 kilometers producing competitive outcomes. Furthermore, the region was partitioned into discrete seismic zones predicated on fault characteristics and seismicity density, further augmenting localized hazard assessments. This is polished. multi-method approach encompassing magnitude conversion, spatial smoothing, and area-specific analysis. Modelling offers a comprehensive framework for seismic hazard preparedness in Lampung, providing useful insights for infrastructure strategic planning and disaster mitigation.